EVALUATION OF TWO BUFFER METHODS FOR THE DETERMINATION OF SOIL BUFFERING CAPACITY - OLUFEMI, T.; ADESANWO , O. O.; AZEEZ, M. O. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
A study was carried out to evaluate two buffer methods for the determination of soil pH buffering capacity. Soil samples (0-15 cm) were collected from four sites with varying land use practices (cacao, plantain, oil palm and cashew plantations) at the Teaching and Research Farm, Obafemi Awolowo University, Ile-Ife, Nigeria. The physical and chemical properties of the samples were determined. Titration method which involves shaking for 1 hour and Equilibration method for 7 days, were used to determine soil pH buffering capacity.  The result of physical and chemical analyses showed textural classes ranging from Sandy Loam to Sandy Clay Loam, soil pH ranged between 4.7 and 6.5. Soil under cacao plantation had the highest values for pH (6.5), organic matter (6.2%) and calcium saturation (32.5%) than soil samples from other sites. There was significant difference in buffering capacities between the two methods, higher values were obtained with equilibration method compared with 1 hour titration method. For instance, buffering capacities of soil samples under the following cropping systems for titration and equilibration method respectively were: cacao (2.61, 5.09) and cashew (1.84, 2.18). In addition, higher correlation coefficient (R2) was recorded for Titration method compared with Equilibration method. Similarly, results from titration method correlated more with the selected soil properties compared to equilibration method for all the soil samples. Similar observation was recorded with calculated lime requirement. Therefore, titration method proved a better way of determining soil pH buffering capacity and estimating lime requirement. However, more detailed study is required to support the results of this study.